2005
DOI: 10.1590/s0074-02762005000700017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Citrus reticulata and Mirazid in treatment of Schistosoma mansoni

Abstract: This work has been carried out to investigate the effect ofCurrent control of the disease by chemotherapeutic agents is impractical because of the common occurrence of re-infection after treatment due to the relative resistance of the larval stages of Schistosoma mansoni to schistosomicide drugs (Silva et al. 2003). Praziquantel, the currently used drug for chemotherapeutic control, was reported to induce hemorrhage in the lung tissue of the host (Flisser & McLaren 1989) The present study is a trial to clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…The present study recorded a significant decrease in SDH activity in S. mansoni-infected mice. This is in agreement with the studies by Hamed and Hetta (2005) and Bashtar et al (2006), which found the same results in bilharzial infection associated Schistosoma toxins that accumulate with the mitochondrial fraction and affect the enzyme activity. SDH is the marker enzyme of the mitochondria (el Gowhary 1993), so any changes in the enzyme activity would be accompanied by changes in the mitochondria.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study recorded a significant decrease in SDH activity in S. mansoni-infected mice. This is in agreement with the studies by Hamed and Hetta (2005) and Bashtar et al (2006), which found the same results in bilharzial infection associated Schistosoma toxins that accumulate with the mitochondrial fraction and affect the enzyme activity. SDH is the marker enzyme of the mitochondria (el Gowhary 1993), so any changes in the enzyme activity would be accompanied by changes in the mitochondria.…”
Section: Discussionsupporting
confidence: 93%
“…LDH 5 's role in anaerobic glycolysis is reduced and this reduction may explain the false higher contribution of LDH 1 and LDH 2 , which are involved in aerobic respiration. This is confirmed by the study of Hamed and Hetta (2005). In addition, Maly and Toranelli (1993) found that H-monomer is supposed to be principally in-volved in the oxidation of lactate and should therefore be predominant in tissues with a high oxygen supply.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Succinate [23,25]. Lactate dehydrogenase (LDH) inhibition was found to be in the direction of lactate oxidation; therefore, lactate was accumulated and glycogen depleted, which confirms the inhibition of aerobic respiration and the stimulation of anaerobic glycolysis [26].…”
Section: Resultsmentioning
confidence: 82%
“…In addition, purine and pyrimidine nucleotides catabolism were also increased, leading to the activation of 5`-nucleotidase, which plays a major role in nucleic acid catabolism. The increased catabolism stimulated the active transport and phagocytosis processes, leading to further activation of 5`-nucleotidase through the plasma membrane where the enzyme is usually localized [23].…”
Section: Resultsmentioning
confidence: 99%